2020
DOI: 10.1111/ijcp.13769
|View full text |Cite
|
Sign up to set email alerts
|

Saxagliptin and vildagliptin lowered albuminuria in patients with diabetes and hypertension independent on glycaemic control

Abstract: Background Preclinical data illustrated that the dipeptidyl peptidase‐4(DPP‐4) inhibitors did lower urinary albumin excretion in diabetes‐induced rats. We evaluated the effects of saxagliptin and vildagliptin on albuminuria in patients with diabetic nephropathy on top of the renin‐angiotensin‐aldosterone system (RAAS) blockade therapy. Methods This study included 120 patients with type 2 diabetes (T2D), hypertension, and prevalent albuminuria [defined as urine albumin‐to‐creatinine ratio (UACR) 30‐3000mg/g cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…A recent RCT demonstrated that the administration of saxagliptin and vildagliptin for 12 weeks significantly reduced the albuminuria rate by 57.9% (95% CI: 66.1-49.8%) and 55.2% (95% CI 64.9-45.4%), respectively, compared with the control group in T2D subjects. Interestingly, these observations were not associated with HbA1c changes [119].…”
Section: Vildagliptinmentioning
confidence: 81%
“…A recent RCT demonstrated that the administration of saxagliptin and vildagliptin for 12 weeks significantly reduced the albuminuria rate by 57.9% (95% CI: 66.1-49.8%) and 55.2% (95% CI 64.9-45.4%), respectively, compared with the control group in T2D subjects. Interestingly, these observations were not associated with HbA1c changes [119].…”
Section: Vildagliptinmentioning
confidence: 81%
“…Evidence showed that saxagliptin and vildagliptin significantly reduced albuminuria, respectively, in diabetic patients with hypertension. Saxagliptin might present a stronger effect on reducing albuminuria compared to vildagliptin, an action independent of glycaemic control [ 19 ]. In fact, administration of saxagliptin ameliorated microalbuminuria in patients with or without renal impairment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%